PRO DAN KONTRA PENAFSIRAN ZAMAKHSYÂRI TENTANG TEOLOGI MU'TAZILAH DALAM TAFSÎR AL-KASYSYÂF - Bustami Saladin (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2010)
In general, the interpretation of the Qur’an is based onthe Sunnah Rasulullah SAW explanation (tafsîr bi alma'tsûr)and the results of the experts thought of ijtihad(tafsîr bi al-ma'qûl) and both must go hand in hand andcomplement each other. Interpretation of the holy versesof the Qur’an have been carried out by the mufassirînfrom various streams such as Sunni, Shi'a and Mu'taziliteand in many ways we see the various differences ofinterpretation that they are doing whether in relation toissues of fiqh, philosophy and related to the verses, andthe different interpretations that they have done issomething that no longer disputed. All the teachings ofIslâm, including about tawhid discussed in the science ofkalam is derived from the Qur’an and the hadits, both ofthe flow Khawarij, Murji'ah, Asy'ariyah, Mu'tazilite, all ofwhich underlie their views with the two-runway, butbecause there are different interpretations of the Qur’anmade by each of these streams then arises the theologicalunderstandings that vary as well.